EFFECTIVENESS OF STEAM EDUCATION WITH SOCIAL MEDIA NETWORKS PROMOTING SCIENTIFIC MIND TOWARDS SCIENCE AMONG MATHAYOMSUKSA 1 STUDENTS - Kantasima , Nuthinee; Udomphol, Boonrudee (Journal of Educational Review Faculty of Education in MCU, 2025)
The objectives of this study were to investigate the Scientific Attitudes of Mathayomsuksa 1 students after receiving learning management based on the STEAM Education approach with the use of online media. The sample in this study consisted of 34 students from Mathayomsuksa 1/2 at Nonsungsritani School, under the Secondary Education Service Area Office, Nakhon Ratchasima, who were studying in the first semester of the academic year 2024 and were selected through simple random sampling. The research instruments used were: 1) a lesson plan based on the STEAM Education approach with the use of social media. 2) a Scientific Attitudes Survey. The results of this study revealed that: The Scientific Attitudes of Mathayomsuksa 1 students who received learning management based on the STEAM Education approach, combined with the use of social media, showed a significant increase after the intervention compared to before, at a significance level of .05.